Combined transcriptomic and metabolomic analysis reveals a role for adenosine triphosphate-binding cassette transporters and cell wall remodeling in response to salt stress in strawberry - Li, Shuangtao; Chang, Linlin; Sun, Rui; Dong, Jing; Zhong, Chuanfei; Gao, Yongshun; Zhang, Hongli; Wei, Lingzhi; Wei, Yongqing; Zhang, Yuntao; Wang, Guixia; Sun, Jian (Frontiers in Plant Science, 2022)
Strawberry (Fragaria × ananassa Duch) are sensitive to salt stress, and breeding salt-tolerant strawberry cultivars is the primary method to develop resistance to increased soil salinization. However, the underlying molecular mechanisms mediating the response of strawberry to salinity stress remain largely unknown. This study evaluated the salinity tolerance of 24 strawberry varieties, and transcriptomic and metabolomic analysis were performed of ‘Sweet Charlie’ (salt-tolerant) and ‘Benihoppe’ (salt-sensitive) to explore salt tolerance mechanisms in strawberry. Compared with the control, we identified 3412 DEGs (differentially expressed genes) and 209 DAMs (differentially accumulated metabolites) in ‘Benihoppe’, and 5102 DEGs and 230 DAMs in ‘Sweet Charlie’. DEGs GO (Gene Ontology) enrichment analyses indicated that the DEGs in ‘Benihoppe’ were enriched for ion homeostasis related terms, while in ‘Sweet Charlie’, terms related to cell wall remodeling were over-represented. DEGs related to ion homeostasis and cell wall remodeling exhibited differential expression patterns in ‘Benihoppe’ and ‘Sweet Charlie’. In ‘Benihoppe’, 21 ion homeostasis-related DEGs and 32 cell wall remodeling-related DEGs were up-regulated, while 23 ion homeostasis-related DEGs and 138 cell wall remodeling-related DEGs were down-regulated. In ‘Sweet Charlie’, 72 ion homeostasis-related DEGs and 275 cell wall remodeling-related DEGs were up-regulated, while 11 ion homeostasis-related DEGs and 20 cell wall remodeling-related DEGs were down-regulated. KEGG (Kyoto Encyclopedia of Genes and Genomes) pathway analyses showed only four KEGG enriched pathways were shared between ‘Benihoppe’ and ‘Sweet Charlie’, including flavonoid biosynthesis, phenylalanine metabolism, phenylpropanoid biosynthesis and ubiquinone and other terpenoid-quinone biosynthesis. Integrating the results of transcriptomic and metabolomics analyses showed that ABC (ATP-binding cassette) transporters and flavonoid pathway genes might play important roles in the salt stress response in strawberry, and DAMs and DEGs related to ABC transporter and flavonoid pathways were differentially expressed or accumulated. The results of this study reveal that cell wall remodeling and ABC transporters contribute to the response to salt stress in strawberry, and that related genes showed differential expression patterns in varieties with different salt tolerances. These findings provide new insights into the underlying molecular mechanism of strawberry response to salt stress and suggest potential targets for the breeding of salt-tolerant strawberry varieties.